2017
DOI: 10.15294/kemas.v12i2.5366
|View full text |Cite
|
Sign up to set email alerts
|

The Needs of Information Services on Reproductive Health, STIs and HIV in Middle Adolescence

Abstract: Reproductive health information including STIs and HIV/AIDS has been provided in community health center. In fact, the level of adolescent knowledge in terms of sexual health and its risks is still low. This study aims to identify adolescent needs of information services on sexual and reproductive health including STIs and HIV/AIDS. All adolescent aged 15 to 19 years in Ngesrep village were recruited as a sample. There were 237 adolescents participated in this cross sectional study. The findings showed that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Therefore, it can be said that smoking behavior begins during childhood and adolescence. 18 This study found that 30% of respondents have smoked, and one-third of smokers were heavy smokers (more than one pack/day). Then, they began smoking since elementary school.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, it can be said that smoking behavior begins during childhood and adolescence. 18 This study found that 30% of respondents have smoked, and one-third of smokers were heavy smokers (more than one pack/day). Then, they began smoking since elementary school.…”
Section: Discussionmentioning
confidence: 74%
“…As a result, poor knowledge about reproductive health encouraged adolescents to engage in premarital sexual activities. 12 The better the reproductive health knowledge, the lower the premarital sexual activity of adolescents. Conversely, the lower the reproductive health knowledge, the higher the chance of adolescents to engage in premarital sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also found the same thing, that adolescents who had permissive attitudes and fall into risky sexual activity were male adolescents aged less than 17 years who had poor knowledge of sexually transmitted infections and HIV. 12 Besides, respondents who conducted sociosexual behavior were those who had exposure to sexuality media. The exposures to sexuality were experienced from real-life experience on daily activities of prostitution environment and of course, because of the massive internet penetration among adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hospitals constituting PMTCT service referral had in fact yet to implemented good medical management to HIV-positive women despite their obligation to provide safe, high-quality, anti-discrimination and effective service by emphasizing more on patient benefit according to the Hospital's standard service (Mirkuzie, 2010;Gumbo, 2011;Rokhmah 2014). In many cases, a variety of medical measures not referring to guidelines, relatively difficult and expensive access, sterilization practice as if compelled, and discrimination by medical personnel were among the challenges in access and service quality of PMTCT (Nasution, 2012;Koye, 2013;Turan, 2013;Isni, 2016;Shaluhiyah, 2017). This research is intended to study the effectiveness of PMTCT service system in Surakarta.…”
Section: Introductionmentioning
confidence: 99%